The academic interest for bioplastics - a bibliometric analysis - Sagapova, Nikola; Cudlinova, Eva (Economics and Environment, 2022)
Plastic materials are shaping modern society and making our lives easier. However, due to improper handling of plastic waste, plastics are no longer ubiquitous only in our homes, villages and cities but also in the natural environment. In line with the concept of bioeconomy, bioplastics are presented as a sustainable option that could help the economy overcome its dependence on fossil fuels and contribute to the reduction of overall plastic pollution. The study aims to identify the areas of academic interest in bioplastics. The study's methodological approach is based on a bibliometric (scientometric) analysis. It was found that in academia, biology, chemistry, and biotechnology are the main areas dealing with bioplastics, focusing on the whole process of product development. At the same time, there is a significant lack of research in areas such as social sciences, including economics. These findings should contribute to the global scientific discourse.